Three-dimensional assessment of low-level laser therapy on orthodontic miniscrew displacement using CBCT: a retrospective study - Dina Alaaeldin Elfouly; Sherief Hussein Abdel-Haffiez; Nadia Mosaad El-Harouni; Mohamed Abdel Sattar Elzoheiry; Eiman Salah Marzouk (BMC Oral Health, 2024)
Abstract Background This study aimed to assess the effect of Low-Level Laser Therapy (LLLT) on sagittal, transverse and vertical Orthodontic miniscrew displacement. Materials and methods The study included CBCTs from the records of 12 adult patients who underwent upper first premolar extraction and canine retraction with orthodontic miniscrews for maximum anchorage. The miniscrews on one side received LLL, while the other side served as a control. The Low-Level Laser was applied to assess its effect on the displacement of the miniscrews. The used CBCTs have been taken at two-time points: immediately after miniscrew insertion (T0) and four months after the start of canine retraction (T1) with a total of 24 CBCTs. Miniscrew displacement was assessed by measuring head (HMS) and tail (TMS) displacement to the axial, coronal and mid-sagittal planes on the CBCT at the two time points. Miniscrews displacement (T1-T0) was compared between LLL side and control side. Comparisons were performed using paired samples t-test. The significance level was set at p-value < 0.05. The reproducibility of measurements was assessed by intraclass correlation coefficient (ICC). Results After four months of canine retraction, HMS and TMS from both laser and control sides showed significant three-dimensional displacement at p < 0.05. No significant difference in mean displacement in the vertical, sagittal, nor transverse planes between both sides was elicited. Conclusion LLL application in the used protocol does not affect the amount of miniscrew displacement in any of the three planes of space. Miniscrew displacement was significant in both groups.